Genetics of acheiropodia (the handless and footless families of Brazil). VI. Formal genetic analysis - Freire-Maia, A.; Freire-Maia, N.; Morton, N. E.; Azevêdo, E. S.; Quelce-Salgado, A. (My University, 1975)
A genetic analysis is presented of data from 22 Brazilian sibships with cases of acheiropodia (the handless and footless families of Brazil). Segregation analysis performed using a 16K CDC 3100 computer showed a segregation frequency of .245 ± .040, which is close to the expected value of .25. No sporadic cases were detected. The ascertainment of the probands was through multiple incomplete selection (pi = .55 ± .07). The data are consistent with the hypothesis of an extremely rare autosomal recessive gene as the etiological factor in acheiropodia. Prevalence is estimated as 29 ± 4, which is the same as the number of high risk cases; gene frequency equals .0009 ± .0005, and the incidence at birth is 4 x 10 -6 by the indirect method or 7 x 10 -6 by the direct method. The frequency of heterozygotes at birth is assumed to be 0.18% (450 times the frequency of affected). Population size is approximately 10 million, and the number of founders on a unique mutation hypothesis is estimated at about 500. All these estimates are first approximations and must be accepted with caution.